The Knowledge and Performance of Nurses Working in Hospitals in Ardabil, Iran, Regarding the Care for Patients With Chest Tube and the Related Factors - Milad Salimian; Mir Hossein Aghaei; Mohammad Hossein Hakimi (نشریه پرستاری ایران)
Background & Aims Nurses play a significant role in maintaining and promoting patient health, and their knowledge and practice in managing complex interventions such as chest tube management for critically ill patients are crucial to prevent complications and accelerate patient recovery. This study aimed to assess the knowledge and performance of nurses working in hospitals in Ardabil, Iran, regarding the provision of care to patients with chest tube, and find the related factors. Materials & Methods This descriptive- correlational study was conducted on 265 nurses working in the ICU, emergency, and surgical wards of hospitals affiliated with Ardabil University of Medical Sciences (AUMS) in 2023. Data were collected using a reliable and valid three-part questionnaire to assess nurses' demographic characteristics, knowledge, and practice regarding chest tube care. The collected data were analyzed in SPSS software, version 23 using descriptive and inferential statistics. Results Overall, nurses' knowledge was at a moderate level (48.28±8.49). Only 12 nurses (4.52%) achieved satisfactory scores. Regarding nursing practice, most nurses (n=259, 97.73%) obtained satisfactory scores. There was a significant correlation between knowledge and practice variables (r=0.170, P=0.003). Nurses' educational level had a significant association with their knowledge (B=3.090, P=0.008) and practice (B=2.299, P=0.010). Conclusion Due to the low number of AUMS nurses with satisfactory knowledge scores regarding the care for patients with chest tube, it is necessary to hold continuous training courses for nurses on effective care for patients with chest tube care in the AUMS hospitals.